Seasonality and diversity of epipelic diatoms in two wetlands of Banglades - Nahar, Khurshid; Khondker, Moniruzzaman; Sultana, Munira (Bangladesh Journal of Botany, 2010)
Seasonality and composition of epipelic diatom community were studied for two years in two wetlands of Bangladesh namely, Joysagar and Sitlai Beel. A total 73 diatom taxa were recorded. The average density of epipelic diatom was higher in Sitlai Beel (52.97 × 104/g sediment) than in the Joysagar (3.92 × 104/g sediment). The epipelic diatom community of Joysagar was dominated by the species of Melosira, Synedra, Navicula, Pinnularia, Gomphonema, and Nitzschia, whereas Melosira, Navicula, Pinnularia, Cymbella and Gomphonema dominated in Sitlai Beel. Melosira granulata, Navicula americana, Pinnularia major, and Gomphonema lanceolatum were dominant and expressed distinct seasonality in both wetlands. The concentration of soluble reactive silicate of water and the average density of epipelic diatom did not express any significant relation in both of the water bodies. The concentration of phytoplankton chl a had a positive relationship with epipelic diatoms and was significant in Sitlai Beel. Key words: Epipelic diatoms; Sitlai Beel; Wetlands; Melosira; Bangladesh DOI: 10.3329/bjb.v39i1.5523 Bangladesh J. Bot. 39(1): 29-36, 2010 (June)